소셜미디어 음식 콘텐츠 이용수준에 따른 20-30대의 건강행동 및 식습관에 대한 단면 조사연구 - 방서연(Seo-Yeon Bang); 정복미(Bok-Mi Jung) (Korean journal of community nutrition, 2023)
Objectives: This study was intended to investigate adults' health behaviors and eating habits according to their levels of social media use. Methods: From May 27 to July 11, 2022, an online survey was conducted of 452 male and female social media users in their 20s and 30s, and their eating habits and health behaviors were compared and analyzed according to their degree of social media use. For each of the three levels of food content use, the frequency of social media content use, and the total score range of average social media viewing time per day were divided into three parts, and a group with a score of less than 2 points was classified as low-use; a group with a score of 2 or more and less than 3 points was classified as middle-use; and a group with a score of 3 points or more was classified as high-use. Results: The use of food content was higher in women than in men (P < 0.001), and higher in those in their 20s than in those in their 30s (P < 0.001). The group with a high level of food content use showed a higher rate of post-use hunger than the group with a low level (P < 0.01). The experience of eating after using food content was also higher in the group with a high level of use than in the group with a low level of use (P < 0.001). The group with a normal or high level of food content use had more negative eating habits than the group with a low level. Conclusions: The study highlighted the need to provide desirable food content to people in their 20s and 30s with negative eating habits and to promote them so that they can use the right healthy nutrition-related content.